Collection of portraits of the Shumack family ([ca.1880-1940], 1880)
Collection of portraits of various members of the Shumack family who were pioneers in the Canberra region.
Photographs individually catalogued and digitised.
Condition: Variable, some discoloration, some fading.
Also available online
National Library of Australia Manuscripts section MS 1643
Samuel Shumack born in Counry Cork, Ireland, arrived in Australia with his family in 1856 at the age of 6. His father, Richard Shumack, was employed by Robert Campbell, Duntroon, then at Gininderra, where Samual also began work as a shepherd. When 16, Samuel Shumack settled on "Springvale", Weetangera, where he lived until his death in 1940.
Keywords: Shumack family -- Photograph collections; Shumack, Samuel, -- 1850-1940 -- Portraits; Shumack, Sarah -- Portraits; Shumack, George, -- Mrs. -- Portraits; Pioneers -- Australian Capital Territory -- Canberra region -- Portraits; Farmers -- Australian Capital Territory -- Canberra Region -- Portraits; Pioneers; Farmers